Ailanthone exerts an antitumor function on the development of human lung cancer by upregulating microRNA‐195. Issue 6 (19th December 2018) - Hou, Shizhen; Cheng, Ziming; Wang, Wenling; Wang, Xiangdong; Wu, Yubing
Abstract: Background: Lung cancer is a common leading cause of cancer‐related death worldwide. Ailanthone, a natural compound isolated from Chinese herb Ailanthus altissima, has been reported to exert antiproliferative effects on various cancer cells. Methods: The present study aimed to investigate the role of ailanthone in the lung cancer cells and the correlation between the ailanthone and microRNA (miR)‐195. The cell viability, proliferation, and apoptosis were determined by cell counting kit‐8 assay, bromodeoxyuridine incorporation method, annexin V‐fluorescein isothiocyanate/propidium iodide assay, respectively. Apoptosis‐ and autophagy‐related proteins, as well as regulatory factors in the signaling pathways, were analyzed by Western blot method. The expression of miR‐195 was quantified by quantitative reverse transcription‐polymerase chain reaction. Results: The results confirmed that ailanthone was involved in the lung cancer cell progress by inhibiting cell viability and proliferation, but promoted cell apoptosis and autophagy. We also found that ailanthone upregulated the expression of miR‐195. Further, the downregulated miR‐195 inhibited the apoptosis and autophagy induced by ailanthone. Moreover, our studies revealed that miR‐195 inhibitor promoted the phosphorylation of PI3K, AKT, JAK, and STAT3, which was inhibited by ailanthone. Conclusion: All these findings suggest that ailanthone plays key roles in lung cancer progress and is closely correlated with miR‐195 expression. Abstract : All these findings suggest that ailanthone plays key roles on lung cancer progress and is closely correlated with miR‐195 expression.